Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.4081/monaldi.2005.636
|View full text |Cite
|
Sign up to set email alerts
|

Extrapleural hematoma: when is surgery indicated?

Abstract: Extrapleural haematoma (EH) is a rare clinical condition of which four cases are presented. Different etiologies were encountered. Identical findings were found on the chest X-ray. Two cases were secondary to spontaneous rib fracture and the other two were iatrogenic. Surgical exploration was necessary in one patient following pleural biopsy. Medical treatment and clinical observation were the treatment of choice in the remaining three stable patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 4 publications
(8 reference statements)
0
30
0
Order By: Relevance
“…Poyraz et al 2 recommended medical therapy or simple observation when the vital signs of the patient are stable and the hematoma is small; and surgical treatment is required if the hematoma is huge, causing circulatory and ventilatory disturbances, or the condition of patient is unstable because of active bleeding, as in our case.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Poyraz et al 2 recommended medical therapy or simple observation when the vital signs of the patient are stable and the hematoma is small; and surgical treatment is required if the hematoma is huge, causing circulatory and ventilatory disturbances, or the condition of patient is unstable because of active bleeding, as in our case.…”
Section: Discussionmentioning
confidence: 90%
“…1 It has been reported that extrapleural hematoma can be caused by chest trauma or iatrogenic complications at the time of central venous catheterization, rupture of an aneurysm of the thoracic aorta, pleural biopsy, or even spontaneous rib fracture. 2 The diagnosis of extrapleural hematoma can be confi rmed by chest radiography. The typical fi nding of extrapleural hematoma is a D-shaped opacity with its base located against the corresponding part of the chest wall.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Among the differential diagnosis are encysted pleural effusion, pleural tumors, peripheral lung tumors, oleothorax, round atelectasis and diaphragmatic hernias. [1,6] …”
Section: Discussionmentioning
confidence: 99%
“…[1] On the other hand, some studies have stated that VATS is the appropriate method to explore the extrapleural area, evacuate the hematoma by opening the parietal pleura and determine the bleeding center. [5,6] We also think that in cases where tube thoracostomy fails to provide adequate drainage and EPH is suspected, VATS should be the first preference. If VATS does not yield good results, then hematoma should be drained with thoracotomy.…”
Section: (A) (B) (C)mentioning
confidence: 99%
“…7 Compared with reported cases of extrapleural hematoma, our case was categorized as a large hematoma, for which surgical removal is usually recommended. 1, 8 We chose close observation rather than another treatment for her extrapleural hematoma because the patient was…”
Section: Discussionmentioning
confidence: 99%